Retoryka i filozofia w korespondencji św. Augustyna z Woluzjanem (Epistulae 132, 135, 137) - Toczko, Rafał (Vox Patrum, 2013)
This paper takes under a detailed scrutiny some passages from the Letters 132, 135 and 137 among the Corpus of Augustine’s correspondence. The author casts some light on the cultural contexts of the Augustinian letters as it is presented in the contemporary research. In the outcome, a new reading of the correspondence with Volusianus is offered. The main thesis argumented for in this study is that what we encounter in these letters is a public philosophical dispute, in which both sides tried to discredit the counterparts as lacking in terms of ethical and strictly professional i.e. philosophical competences. The stake is the spiritual and intellectual authority of Augustine and the validity of Christian philosophy, especially of the Christian concept of divinity and its presence.